Interpersonal Needs and Dysfunctional Self-Focus Mediate the Effect of Dysfunctional Pandemic Grief on Suicidality Among Nursing Professionals Who Witnessed Patients’ Deaths - Park C. Hyung Keun; Makhour Hussein; Ahn Junseok; Jun Jin Yong; Park Jangho; Chung Seockhoon (Journal of Korean medical science, 2025)
Background: We aimed to explore whether the dysfunctional pandemic grief of nursing professionals who experienced a patient’s death may be related with their suicidal ideation and examine whether their interpersonal problems and dysfunctional self-focus mediate this association. Methods: An anonymous online survey was conducted on November 16–18, 2023 among nurses in a tertiary hospital who witnessed people’s death. Their psychological states were assessed using the Pandemic Grief Scale (PGS) for healthcare workers, Dysfunctional Selffocus Attributes Scale (DSAS), Interpersonal Needs Questionnaire (INQ), and Depressive Symptom Inventory-Suicidality Subscale (DSI-SS). Linear regression analysis was conducted to explore the expecting variables for the DSI-SS. Mediation analysis was performed to examine the mediating effects of self-focus and interpersonal problems between grief reaction and suicidal ideation. Results: The PGS (β = 0.18, P = 0.005), INQ-Perceived Burdensomeness (INQ-PB; β = 0.51, P < 0.001), and DSAS-Negatively Biased Focus (DSAS-NBF; β = 0.17, P = 0.021) were significantly associated with the DSI-SS. Mediation analysis using these variables showed that the PGS directly influenced the DSI-SS, and the INQ-PB and DSAS-NBF partially mediated the influence of the PGS on DSI-SS. Conclusion: Dysfunctional grief experienced by nurses following the loss of patients during the pandemic exacerbated suicidal ideation by fostering a greater focus on negative outcomes and heightened feelings of being a burden. These findings underscore the need for targeted interventions to address these specific cognitive and emotional vulnerabilities to mitigate the risk of suicidal ideation. KCI Citation Count: 0